Brucella-positive raw milk cheese sold on the inner European market: A public health threat due to illegal import?. (June 2019) - Jansen, Wiebke; Linard, Catherine; Noll, Matthias; Nöckler, Karsten; Al Dahouk, Sascha
Abstract: Travel and migration are the major drivers of human brucellosis in Western Europe. The infection is usually transmitted through the consumption of unpasteurized milk or dairy products in or from endemic regions. Although eradicated from livestock in Germany and most Member States of the European Union, considerable numbers of domestic human brucellosis cases have been reported annually. The actual source of these autochthonous cases in non-endemic countries remains to be elucidated. We therefore evaluated the presence of Brucella spp. in 200 cheese samples originating from endemic countries which were sold at weekly markets, in supermarkets and by delis in Berlin (Germany) as well as online. The cheese samples included loose, non-labelled and pre-packed, labelled cheese of five types (brine, cream, soft, semi-hard and hard cheese), made from bovine, ovine and caprine milk. The cheese was mainly declared as raw milk cheese by the retailers. We screened for and confirmed the presence of Brucella -DNA in cheese using genus-specific quantitative real-time PCRs targeting IS711 and bcsp31, respectively. The molecular prevalence of Brucella was 20.5% (n = 41), but viable Brucellae could not be isolated from the positively tested samples using classical culture methods. The logistic regression model indicated that Brucella was significantly more often detected in late summer purchases (p = 0.036) as well as in cheese from Bulgaria, France, Greece and Turkey (p = 0.017). In contrast to the vendor information, essentially only three positive cheese samples were made from raw milk. Moreover, positive samples clustered at certain vendors which indicates large-scale illegal imports. In summary, Brucella in imported raw milk cheese seems to be still a challenge for food safety standards in the European Union. Uncontrolled import of dairy products from endemic regions might explain human Brucella infections acquired in non-endemic EU countries. Highlights: Brucella -positive raw milk cheese is available at German retail level. Brucellosis is still a foodborne zoonosis in non-endemic countries. Uncontrolled imports of cheese do not comply with food safety standards.